2005
DOI: 10.1097/00008483-200505000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Life-Years Gained From Modern Cardiological Treatments and Population Risk Factor Changes in England and Wales, 1981–2000

Abstract: Objectives. We estimated life-years gained from cardiological treatments and cardiovascular risk factor changes in England and Wales between 1981 and 2000.Methods. We used the IMPACT model to integrate data on the number of coronary heart disease patients, treatment uptake and effectiveness, risk factor trends, and median survival in coronary heart disease patients.Results. Compared with 1981, there were 68 230 fewer coronary deaths in 2000. Approximately 925 415 life-years were gained among people aged 25-84 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
2
32
0
1
Order By: Relevance
“…40 Previous studies in the United Kingdom and United States suggested that modest changes in major population risk factors (notably smoking, lipid levels, and hypertension) have had the greatest effect in decreasing IHD mortality, but increases in obesity, diabetes, and sedentary lifestyles threaten to undermine these trends. [40][41][42][43][44] A similar trend toward lower mortality from cerebrovascular disease in both men and women has been found in developed countries such as the United Kingdom, Sweden, Switzerland, Germany, New Zealand, and Australia and in some developing countries (except Russia).…”
Section: Risk Factor Prevalence and Burden In Developed And Developinsupporting
confidence: 60%
See 1 more Smart Citation
“…40 Previous studies in the United Kingdom and United States suggested that modest changes in major population risk factors (notably smoking, lipid levels, and hypertension) have had the greatest effect in decreasing IHD mortality, but increases in obesity, diabetes, and sedentary lifestyles threaten to undermine these trends. [40][41][42][43][44] A similar trend toward lower mortality from cerebrovascular disease in both men and women has been found in developed countries such as the United Kingdom, Sweden, Switzerland, Germany, New Zealand, and Australia and in some developing countries (except Russia).…”
Section: Risk Factor Prevalence and Burden In Developed And Developinsupporting
confidence: 60%
“…54 Similarly, mortality models in England and Wales showed that more than half of the decline (58%) in CVD mortality between 1981 and 2000 was attributable to reductions in population risk factors (primarily smoking, cholesterol, and blood pressure), and 42% was due to medical and surgical treatments. 41 Changes in risk factors explained almost all the decline in CVD mortality in the 1970s in Finland and 53% of the decline between 1982 and 1997. 55 National smoking bans in the early years of the 21st century have led to reductions in acute coronary events.…”
Section: Implications For Population-based/public Health and Individumentioning
confidence: 99%
“…23,32 In England the shift was even starker: from 42 percent and 58 percent to 21 percent and 79 percent. 22,33 Why the difference? IMPACT calculated lifeyears gained by multiplying the number of deaths prevented by the median survival after the intervention.…”
Section: Models and Their Discontentsmentioning
confidence: 99%
“…24 Analyses of life-years gained erased the "other" altogether. 32,33 When one epidemiologist pointed out that the analysis of the United States had ignored the important role played by reduced air pollution, 37 Capewell and his coauthor offered a complex response. Although air pollution and other risk factors might account for the 9 percent unexplained, it was also possible that "imprecision in the measurement and modeling of the major risk factors (cholesterol, smoking, and blood pressure) might also account for much of the gap."…”
Section: Models and Their Discontentsmentioning
confidence: 99%
“…However, it is now clear that the stroke prevention efficacy of medical intervention has steadily and significantly improved over the last 30 years and continues to improve, 10-14 consistent with other observed falls in risk of stroke, [15][16][17] heart attack, and sudden death. 18 Currently used benchmarks for a stroke prevention benefit from CEA over medical intervention (a 30-day procedural risk of stroke/death of 3% for asymptomatic carotid stenosis 19 or 6% for symptomatic carotid stenosis) 20 are outdated. Therefore, the demonstration of stroke prevention equivalence between CAS and CEA using these benchmarks (even if this had been achieved) would be insufficient to justify a current, routine practice indication for CAS.…”
mentioning
confidence: 99%